Adolescent Female Cannabinoid Exposure Diminishes the Reward-Facilitating Effects of Δ9-Tetrahydrocannabinol and d-Amphetamine in the Adult Male Offspring - George Panagis; George Pitsilis; Dimitrios Spyridakos; George G. Nomikos (Frontiers Media S.A., 2017)
Marijuana is currently the most commonly abused illicit drug. According to recent studies, cannabinoid use occurring prior to pregnancy can impact brain plasticity and behavior in future generations. The purpose of the present study was to determine whether adolescent exposure of female rats to Δ9-tetrahydrocannabinol (Δ9-THC) induces transgenerational effects on the reward-facilitating effects of Δ9-THC and d-amphetamine in their adult male offspring. Female Sprague-Dawley rats received Δ9-THC (0.1 or 1 mg/kg, i.p.) or vehicle during postnatal days 28-50. As adults, females were mated with drug-naïve males. We then assessed potential alterations of the Δ9-THC's (0, 0.1, 0.5, and 1 mg/kg, i.p.) and d-amphetamine's (0, 0.1, 0.5, and 1 mg/kg, i.p.) reward-modifying effects using the curve-shift variant of the intracranial self-stimulation (ICSS) procedure in their adult male F1 offspring. The reward-facilitating effect of the 0.1 mg dose of Δ9-THC was abolished in the F1 offspring of females that were exposed to Δ9-THC (0.1 or 1 mg/kg), whereas the reward-attenuating effect of the 1 mg dose of Δ9-THC remained unaltered. The reward-facilitating effects of 0.5 and 1 mg of d-amphetamine were significantly decreased in the F1 offspring of females that were exposed to Δ9-THC (1 mg/kg and 0.1 or 1 mg, respectively). The present results reveal that female Δ9-THC exposure during adolescence can diminish the reward-facilitating effects of Δ9-THC and d-amphetamine in the adult male offspring. These transgenerational effects occur in the absence of in utero exposure. It is speculated that Δ9-THC exposure during female adolescence may affect neural mechanisms that are shaping reward-related behavioral responses in a subsequent generation, as indicated by the shifts in the reward-facilitating effects of commonly used and abused drugs.